Investigating the Determinants of Toxoplasma gondii Prevalence in Meat: A Systematic Review and Meta-Regression. - Simone Belluco; Marzia Mancin; Daniele Conficoni; Giulia Simonato; Mario Pietrobelli; Antonia Ricci (PLoS ONE)
Background Toxoplasma gondii is one of the most widespread parasites in humans and can cause severe illness in immunocompromised individuals. However, its role in healthy people is probably under-appreciated. The complex epidemiology of this protozoan recognizes several infection routes but consumption of contaminated food is likely to be the predominant one. Among food, consumption of raw and undercooked meat is a relevant route of transmission, but the role of different meat producing animal species and meats thereof is controversial. Objectives The aim of the present work is to summarize and analyse literature data reporting prevalence estimates of T. gondii in meat animals/meats. Data sources We searched Medline, Web of Science, Science Direct (last update 31/03/2015). Eligibility criteria Relevant papers should report data from primary studies dealing with the prevalence of T. gondii in meat from livestock species as obtained through direct detection methods. Meta-analysis and meta-regression were performed. Results Of 1915 papers screened, 69 papers were included, dealing mainly with cattle, pigs and sheep. Pooled prevalences, based on random-effect models, were 2.6% (CI95 [0.5-5.8]) for cattle, 12.3% (CI95 [7.6-17.8]) for pigs and 14.7% (CI95 [8.9-21.5]) for sheep. Due to the high heterogeneity observed, univariable and multivariable meta-regression models were fitted showing that the geographic area for cattle (p = 0.032), the farming type for pigs (p = 0.0004) and the sample composition for sheep (p = 0.03) had significant effects on the prevalences of Toxoplasma detected/estimated. Moreover, the role of different animal species was dependent on the geographic location of animals' origin. Limitations Limitations were due mainly to a possible publication bias. Conclusions and implications The present work confirms the role of meat, including beef, as T. gondii sources, and highlights the need for a control system for this parasite to be implemented along the meat production chain. Moreover, consumer knowledge should be strengthened in order to reduce the impact of disease.